1989
DOI: 10.1111/j.1467-6494.1989.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Painting Group Portraits: Studying Life Outcomes for Aggressive and Withdrawn Children

Abstract: Aggression and social withdrawal have long been of interest to personality psychologists. The present article presents a longitudinal study of the development of children selected from a community sample who were high on aggression and withdrawal. The selection of outcome variables is discussed, and outcomes during adolescence are described. For both males and females, high aggressiveness was predictive of low intelligence, poor school achievement, and psychiatric problems. For females, high aggressiveness was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 49 publications
2
14
0
1
Order By: Relevance
“…Children with low intellectual abilities had difficulty leaming needed skills for nonaggressive problem solving and probably experienced increased frustration and stress. Several other studies have shown that intelligence and scholastic achievement are negatively correlated with aggression and delinquency for both boys and girls (Huesmann et al, 1984;Jarvelin, Laara, Rantakallio, Moilanen, & Isohanni, 1994;Moskowitz & Schwartzman, 1989). These relationships are likely to be bidirectional.…”
Section: Other Cognitive Mediatorsmentioning
confidence: 94%
“…Children with low intellectual abilities had difficulty leaming needed skills for nonaggressive problem solving and probably experienced increased frustration and stress. Several other studies have shown that intelligence and scholastic achievement are negatively correlated with aggression and delinquency for both boys and girls (Huesmann et al, 1984;Jarvelin, Laara, Rantakallio, Moilanen, & Isohanni, 1994;Moskowitz & Schwartzman, 1989). These relationships are likely to be bidirectional.…”
Section: Other Cognitive Mediatorsmentioning
confidence: 94%
“…For example, children identified as withdrawn during their early school years tend to underestimate their capabilities and overstress their poor achievements in adolescence (Moskowitz and Schwartzman 1989). Due to relative deficits in social knowledge and skills from childhood, shy adolescents continue to respond poorly towards social situations, placing them in further isolation (Rubin and Stewart 1996).…”
Section: Adolescents and Social Functionsmentioning
confidence: 99%
“…In concert with these findings, Power, Manor and Fox (1991) found that teacher-rated behaviour problems at age 16 predicted various indices of poor health at age 23 in a British cohort. However, Moskowitz and Schwartzman (1989) failed to support these findings for boys, using a longitudinal French-Canadian cohort of boys and girls who were studied in grades one, four and seven and then again during adolescence. And, Farrington (1995) who followed a British male cohort between the ages of 8 and 32 years concluded that while offending (i.e.…”
mentioning
confidence: 93%
“…Donovan, Jessor, & Costa, 1991;Kulbok, Earls, & Montgomery, 1988;Terre, Ghiselli, Taloney, & DeSouza, 1992) or begin during adolescence and follow the subjects into adulthood (Friedman et al, 1993;Sweeting & West, 1995). One exception is the study reported by Moskowitz and Schwartzman (1989) who combined cross-sectional and longitudinal techniques. Aggressive and withdrawn children were followed from grades one, four and seven for five to seven years after identification.…”
mentioning
confidence: 99%